Development Of Numeracy Literacy Through Learning Video On Tiktok Media - Ammy, Putri Maisyarah; Puspita, Ananda; Azis, Zainal (JTMT: Journal Tadris Matematika, 2024)
This study aims to develop students' numeracy literacy based on learning videos on TikTok, so that students are expected to be more interested in learning and better understand mathematical concepts and be able to apply the material in everyday life. The development model used in this study is R&D (Research and Development). This study involved 33 respondents consisting of 3 validators (2 lecturers and 1 teacher), and 30 students. The results of this study indicate that the development of numeracy literacy based on learning videos on TikTok media has received input from validators and mathematics educators with the category "very valid"